Vitamin and water requirements of dairy sheep - Fulvia Bovera; Monica Isabella Cutrignelli; Giuseppe Moniello; Federico Infascelli (Italian Journal of Animal Science, 2010)
The authors review the physiological role and the daily requirement of fat-soluble vitamins (A, D, E and K), vitamin C  and water in dairy sheep. Regarding the vitamins, classical clinical symptoms and/or non-specific parameters, such as  lowered production and reproduction rates are associated with their deficiencies or excesses. Until the last decade,  these compounds were considered important only for the prevention of such alterations; currently, there is more  emphasis on their function as the vitamins can play a key role in optimising animal health. In this respect, of particu-  lar interest is the action of the antioxidant vitamins (especially vitamin C, vitamin E and beta-carotene) in improving  the efficiency of the immune system.